2011
DOI: 10.1158/0008-5472.can-10-1513
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell Invasion Is Promoted by Interstitial Flow-Induced Matrix Priming by Stromal Fibroblasts

Abstract: Interstitial flow emanates from tumors into the microenvironment where it promotes tumor cell invasion. Fibroblasts are key constituents of the tumor stroma that modulate the mechanical environment by matrix remodeling and contraction. Here, we explore how interstitial fluid flow affects fibroblast-tumor cell interactions. Using a 3-dimensional invasion assay and MDA-MB-435S cells cocultured with dermal fibroblasts in a collagen matrix, we showed a synergistic enhancement of tumor cell invasion by fibroblasts … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(137 citation statements)
references
References 47 publications
4
129
0
Order By: Relevance
“…In the culture chamber, we found that the fluid flow speed was less than 1 μm/s, over 100 times lower than in the side channels and comparable to physiologic level of interstitial flow, about 0.5 μm/s (Fig. 1C) (26).…”
Section: Resultsmentioning
confidence: 66%
“…In the culture chamber, we found that the fluid flow speed was less than 1 μm/s, over 100 times lower than in the side channels and comparable to physiologic level of interstitial flow, about 0.5 μm/s (Fig. 1C) (26).…”
Section: Resultsmentioning
confidence: 66%
“…VEGF-C also induces TGFb secretion by LECs (J. Munson and M. Swartz, unpublished data), which can promote regulatory T-cell education and drives fibroblast-to-myofibroblast transformation and stromal stiffening. Finally, increased interstitial flow in the tumor stroma due to high pressure gradients at the tumor margin also promotes TGFb activation, myofibroblast transformation, and stromal stiffening (44), and promote fibroblast-led tumor-cell invasion (45). Drawings are courtesy of Katie Hubbell, University College London, UK.…”
Section: Lymph Flow Of Antigensmentioning
confidence: 99%
“…13,44 In this case, the leader cells, which can be activated stromal fibroblasts or cancer cells themselves, 15 initiate and promote collective invasion of follower cells in a cell-cell contact dependent manner. This strand-like collective invasion widens the microtracks to become macropatterns that further enables directed invasion of the following cell mass.…”
Section: Discussionmentioning
confidence: 99%
“…51 Moreover, despite the intriguing invasion behavior of cancer cells themselves, the role of fibroblasts in priming local ECM microenvironment for cancer invasion has been increasingly recognized. 44 It will be highly instructive to conduct co-culture of fibroblasts and invasive cells and quantitative assays such as those performed in this study to further understand the potential feedback mechanism between the two cell types.…”
Section: Discussionmentioning
confidence: 99%